Adjustment of Daily Activities: the Influence of Smartphone Adoption on the Travel Pattern of Mobile Professionals in the Greater Jakarta Area - Gloriani Novita Christin; Ofyar Z. Tamin; Idwan Santosa; Miming Miharja (Journal of Engineering and Technological Sciences, 2014)
The  swift  augmentation  in  the  adoption  of  smartphones,  the  gadget that  resulted  from  the  convergence  of  Information  and  Communication Technology  (ICT),  potentially  transforms  people's  life  in  myriad  dimensions. One  potential  change  induced  by  smartphones,  is  how  people  restructure  their daily agenda and consecutively influence their travel pattern. To understand it, this study theoretically reviews  mobile professional work, smartphone adoption, and how people conduct their mobile interaction, planning and execution of daily activities. Mobile professionals, the  cohort of professionals  that spend more than 20% of their total working time moving  around out  of  their work environment; they  are  important  beneficiaries  of  smartphones  and   have  been  chosen  as  the target of  this  study. Empirical results of mobile professionals´ experiences in the Greater Jakarta Area are presented at this juncture. Furthermore, their adjustment of  activities  as  a  dynamic  response  to  receiving  extensive  information  via smartphones  is  also  analysed.  The  results  indicate  that  there  is  a  strong adjustment  of  daily  activities  by  mobile  professionals.  Through  those  changes, the transformation of daily travel patterns  related to the activity is  also  brought about by the use of this high-end ICT contrivance.